Pengurusan tekanan kerja dikalangan guru sekolah rendah di zon Sungai Balang, daerah Muar - Mohamad, Hafiz Fahmi (2014)
This research discusses the management of job stress among primary school teachers in the zone of the Sungai Balang, Muar. Stress management level was measured by the four causes of teacher stress management aspects of student discipline, curriculum management, the management of the school environment and interpersonal relationships among teachers. The study was conducted using a quantitative method which involves 197 samples for quantitative data. The questionnaire was used in this study. Results from the analysis showed that all levels of work stress management showed moderate overall mean score of 3.540 and a standard deviation of 0.352. Apart from the source of stress in terms of the school environment are high that the mean score of 3.979 and a standard deviation of 0.933. It is hoped that this research will benefit headmasters and teachers in order to identify the causes of stress in primary school teachers and also to find ways to overcome work stress factors.